Gender differences in perceiving, coping and managing occupational stress a study among teachers of Taft, Samar Leyte - Mondia, Grace N. (2012)
The study examines the stressors, burnout levels, effects of stress, and the coping mechanisms of teachers in Taft., Eastern Samar based on their gender and marital status. With a sample size of 115, and using a combination of quantitative (survey), qualitative (FGD and in-depth interview) and feminist perspective as methodologies, the research reveals that occupational stress affect both men and women. However, differences between men and women's responses to stress and severity of stress were noted. Women's stress was aggravated by the multiple roles they perform in their homes and at work. Women suffer from unique stressors;thus, it is important to acknowledge these stressors in order to understand women's specific needs and employ suitable stress management programs. The government, school administrators, parents and private individuals are encouraged to work hand-in-hand to address the educational issues cited in this paper.